An Overview of Research Into the Use of Ice for Cooling Deep Mines - Sheer T. J (The Australasian Institute of Mining and Metallurgy, 1988)
The increasing demand for underground cooling in South African gold mines has resulted in various cooling methods being con- sidered, including the use of ice. Two main areas in connection with ice cooling systems are being investigated. The first concerns the efficient and cost effective production of ice on a larger scale than previously required for any other application. The second con- cerns the transportation of ice in pipes from surface ice-making machines to underground melting sites.